Respuesta :
ANSWER
The value of the expression is
[tex] - 1[/tex]
EXPLANATION
Method 1: Rewrite as product of
[tex]{i}^{2} [/tex]
The expression given to us is,
[tex] {i}^{0} \times {i}^{1} \times {i}^{2} \times {i}^{3} \times {i}^{4} [/tex]
We use the fact that
[tex]{i}^{2} = - 1[/tex]
to simplify the above expression.
[tex] {i}^{0} \times {i}^{1} \times {i}^{2} \times {i}^{3} \times {i}^{4} = {i}^{0} \times {i}^{1} \times {i}^{3} \times {i}^{2} \times {i}^{4} [/tex]
This implies,
[tex] {i}^{0} \times {i}^{1} \times {i}^{2} \times {i}^{3} \times {i}^{4} = {i}^{0} \times {i}^{2} \times {i}^{2} \times {i}^{2} \times {i}^{2} \times {i}^{2} [/tex]
We substitute to obtain,
[tex] {i}^{0} \times {i}^{1} \times {i}^{2} \times {i}^{3} \times {i}^{4} = 1\times - 1 \times - 1 \times - 1\times - 1 \times - 1[/tex]
[tex] {i}^{0} \times {i}^{1} \times {i}^{2} \times {i}^{3} \times {i}^{4} = 1\times 1 \times 1 \times - 1 = - 1[/tex]
Method 2: Use indices to solve.
[tex] {i}^{0} \times {i}^{1} \times {i}^{2} \times {i}^{3} \times {i}^{4} = {i}^{0 + 1 + 2 + 3 + 4} [/tex]
This implies that,
[tex] {i}^{0} \times {i}^{1} \times {i}^{2} \times {i}^{3} \times {i}^{4} = {i}^{10} [/tex]
[tex] {i}^{0} \times {i}^{1} \times {i}^{2} \times {i}^{3} \times {i}^{4} = ( {{i}^{2}} )^{5} [/tex]
[tex] {i}^{0} \times {i}^{1} \times {i}^{2} \times {i}^{3} \times {i}^{4} = ( - 1 )^{5} = - 1[/tex]
The value of the expression is
[tex] - 1[/tex]
EXPLANATION
Method 1: Rewrite as product of
[tex]{i}^{2} [/tex]
The expression given to us is,
[tex] {i}^{0} \times {i}^{1} \times {i}^{2} \times {i}^{3} \times {i}^{4} [/tex]
We use the fact that
[tex]{i}^{2} = - 1[/tex]
to simplify the above expression.
[tex] {i}^{0} \times {i}^{1} \times {i}^{2} \times {i}^{3} \times {i}^{4} = {i}^{0} \times {i}^{1} \times {i}^{3} \times {i}^{2} \times {i}^{4} [/tex]
This implies,
[tex] {i}^{0} \times {i}^{1} \times {i}^{2} \times {i}^{3} \times {i}^{4} = {i}^{0} \times {i}^{2} \times {i}^{2} \times {i}^{2} \times {i}^{2} \times {i}^{2} [/tex]
We substitute to obtain,
[tex] {i}^{0} \times {i}^{1} \times {i}^{2} \times {i}^{3} \times {i}^{4} = 1\times - 1 \times - 1 \times - 1\times - 1 \times - 1[/tex]
[tex] {i}^{0} \times {i}^{1} \times {i}^{2} \times {i}^{3} \times {i}^{4} = 1\times 1 \times 1 \times - 1 = - 1[/tex]
Method 2: Use indices to solve.
[tex] {i}^{0} \times {i}^{1} \times {i}^{2} \times {i}^{3} \times {i}^{4} = {i}^{0 + 1 + 2 + 3 + 4} [/tex]
This implies that,
[tex] {i}^{0} \times {i}^{1} \times {i}^{2} \times {i}^{3} \times {i}^{4} = {i}^{10} [/tex]
[tex] {i}^{0} \times {i}^{1} \times {i}^{2} \times {i}^{3} \times {i}^{4} = ( {{i}^{2}} )^{5} [/tex]
[tex] {i}^{0} \times {i}^{1} \times {i}^{2} \times {i}^{3} \times {i}^{4} = ( - 1 )^{5} = - 1[/tex]
- 1
Further explanation
This is a problem that is partly related to complex numbers, i.e., imaginary numbers. We will see how the power of i is an imaginary unit. Maybe we will see an interesting pattern.
[tex]\boxed{\boxed{ \ i = \sqrt{-1}\ }} \rightarrow \boxed{\boxed{ \ i^2 = -1 \ }}[/tex]
Question:
The value of the expression [tex]\boxed{ \ i^0 \times i^1 \times i^2 \times i^3 \times i^4 \ }[/tex]
The Process
Recall [tex]\boxed{ \ x^0 = 1 \ }[/tex].
[tex]\boxed{ \ i^0 = 1 \ }[/tex]
[tex]\boxed{ \ i^1 = \sqrt{-1} \ or \ i \ }[/tex]
[tex]\boxed{ \ i^2 = (\sqrt{-1})^2 = -1 \ }[/tex]
[tex]\boxed{ \ i^3 = i \times i^2 = i \times -1 = -i \ }[/tex]
[tex]\boxed{ \ i^4 = i^2 \times i^2 = -1 \times -1 = 1\ }[/tex]
Then [tex]\boxed{ \ i^0 \times i^1 \times i^2 \times i^3 \times i^4 = 1 \times i \times (-1) \times -i \times 1 \ }[/tex]
[tex]\boxed{ \ i^0 \times i^1 \times i^2 \times i^3 \times i^4 = -1 \times -i^2 \ }[/tex]
[tex]\boxed{ \ i^0 \times i^1 \times i^2 \times i^3 \times i^4 = i^2 \ }[/tex]
The result is [tex]\boxed{\boxed{ \ -1 \ }}[/tex]
- - - - - - -
Another method is to use the property of indices.
[tex]\boxed{ \ x^a \cdot x^b \rightleftharpoons x^{a+b} \ } \ and \ \boxed{ \ (x^a)^b) \rightleftharpoons x^{ab} \ } [/tex]
[tex]\boxed{ \ i^0 \times i^1 \times i^2 \times i^3 \times i^4 = i^{0 + 1 + 2 + 3 + 4} \ }[/tex]
[tex]\boxed{ \ i^0 \times i^1 \times i^2 \times i^3 \times i^4 = i^{10} \ }[/tex]
[tex]\boxed{ \ i^0 \times i^1 \times i^2 \times i^3 \times i^4 = (i^2)^5 \ }[/tex]
[tex]\boxed{ \ i^0 \times i^1 \times i^2 \times i^3 \times i^4 = {-1}^5 \ }[/tex]
We get the same result, i.e., [tex]\boxed{\boxed{ \ -1 \ }}[/tex]
- - - - - - -
Well, now pay attention to the pattern.
[tex]\boxed{ \ i^0 = 1 \ }[/tex]
[tex]\boxed{ \ i^1 = i \ }[/tex]
[tex]\boxed{ \ i^2 = -1 \ }[/tex]
[tex]\boxed{ \ i^3 = -i \ }[/tex]
[tex]\boxed{ \ i^4 = 1\ }[/tex]
[tex]\boxed{ \ i^5 = i^2 \times i^3 = i \ }[/tex]
[tex]\boxed{ \ i^6 = i^2 \times i^4 = -1 \ }[/tex]
[tex]\boxed{ \ i^7 = i^2 \times i^5 = -i \ }[/tex]
Pattern repeat every [tex]4^{th}[/tex] power.
Learn more
- About complex numbers https://brainly.com/question/1658190
- The piecewise-defined functions brainly.com/question/9590016
- The composite function brainly.com/question/1691598
Keywords: what is the value of the expression, i⁰ × i¹ × i² × i³ × i⁴, imaginary number, unit, a complex number, the pattern, the property of indices